Tribological properties of DLC and GLC coating for automotive engine components application under lubrication - Al-Samarai, Riyadh A.; Al-Douri, Y. (Zielona Góra: Uniwersytet Zielonogórski)
Modern automotive designs are needed to increase mechanical and thermal loads that have longer lifespans and are lighter. The power transmissions and motors often use low-friction hard coatings to prevent wear and reduce friction. The Cr-doped graphite-like carbon method is employed for evaluating coating friction and responses to chromium-doped graphite-like carbon (Cr-GLC) under lubrication. Cr-GLC coatings and chromium-doped diamond-like carbon (Cr-DLC) coatings are arranged using physical vapor deposition (PVD) and plasma-enhanced chemical vapor deposition (PECVD), respectively.
Keywords: engine components; complex coatings; Cr-GLC; Cr-DLC; lubrication